Environmentally sustainable chemical treatment of plant fibers for improved performance of polymeric composites. Issue 10 (17th June 2022) - Das, Partha Pratim; Manral, Ankit; Ahmad, Furkan; Sharma, Bhasha; Chaudhary, Vijay; Gupta, Sumit; Gupta, Pallav
Abstract: The present study compares the results of two different chemical treatments of plant fibers reinforcement in terms of mechanical performance and their environmental impact considering sustainability. Jute/Hemp/Flax and their hybrid bidirectional mats were treated separately with two different chemicals namely sodium hydroxide (NaOH) and sodium bicarbonate (NaHCO3 ). The impact of the treatments on the mechanical performance of developed polymeric composites was found to be positive when compared to non‐treated fiber‐reinforced composites. Alkaline treatment showed better mechanical properties as compared to sodium bicarbonate treatment while using a low concentration solution, but the situation was reversed when a higher concentration solution was used. The present study also compares the pH value of the residue chemical solution after both the treatments which is a direct indicator of the acidic level present in the solution. Interestingly, the pH value of the residue chemical solution after the sodium bicarbonate treatment of the fibers was found in the neutral range indicating that the solution is not harmful to the environment and helps in maintaining sustainability while disposing of after the treatment. On the other hand, the ph value (measure using a pH meter) of the sodium hydroxide solution was in the strong alkaline indicating harmful effects in the disposing area. The environmentally friendly treatment of natural fibers with sodium bicarbonate could have a large commercial potential for polymeric composites for various applications.